Ethnographic Study of Social Harmonization between Indigenous Communities and Immigrant Communities in Cahaya Negeri Village - Rahmad Ellen Herdiansyah; M. Ilham Gilang; Ahmad Suradi (IAIN Madura, 2026)
This ethnographic study examines social harmony between the Serawai indigenous community and the immigrant population in Cahaya Negeri Village, Seluma Regency, Bengkulu Province. Using Spradley's ethnographic framework consisting of domain analysis, taxonomy, components, and cultural themes data were collected through participant observation, semi-structured interviews with ten purposively selected informants, and documentation. Findings indicate that interaction patterns are harmonious and associative, supported by a local social contract, cross-ethnic reciprocal cooperation, and 25 years of uninterrupted interfaith activities. Key barriers include language differences, cultural gaps, structural limitations in inter-village activities, population growth, and psychological distance. Solutions center on intensifying communal activities, strengthening religious cohesion, developing adaptive attitudes, and optimizing village governance. Four cultural themes underlie the harmonization: the local social contract, unity in diversity, religion as a transcendent bridge, and harmonization as a collective effort. These findings have implications for Education for Sustainable Development, particularly SDG 4, SDG 10, and SDG 16, suggesting that local wisdom systems can inform multicultural education frameworks and national resilience policies